STEAM+X in Mathematics Education: A Systematic Literature Review - Muhamad Galang Isnawan; Marcel David Pochulu; Javier García-García; Naif Mastoor Alsulami; Sudirman Sudirman (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study analyses how the STEAM+X framework has been implemented in mathematics education. The “X” component represents additional disciplines beyond the traditional STEAM fields, such as culture, history, and architecture. The systematic literature review (SLR) follows the PRISMA protocol. The initial search returned 350,190 documents, but only one article met the rigorous inclusion criteria focused explicitly on STEAM+X in mathematics education. This finding underscores the topic’s novelty and the need for further research. The selected study highlights the integration of geometry, digital and physical technologies (e.g., GeoGebra, AR/VR, 3D printing), and educational levels, including high school and teacher education. The analysis reveals limited implementation across countries and a lack of diversity in content areas. These results call for expanded investigations into STEAM+X practices incorporating broader mathematical domains, varied cultural contexts, and more inclusive educational levels.